Nucleus accumbens D1-receptors regulate and focus transitions to reward-seeking action - Grima, L; Panagi, M; Harmson, O; Syed, E; Manohar, S; Husain, M; Walton, M (Springer Nature, 2022)
It is well established that dopamine transmission is integral in mediating the influence of reward expectations on reward-seeking actions. However, the precise causal role of dopamine transmission in moment-to-moment reward-motivated behavioral control remains contentious, particularly in contexts where it is necessary to refrain from responding to achieve a beneficial outcome. To examine this, we manipulated dopamine transmission pharmacologically as rats performed a Go/No-Go task that required them to either make or withhold action to gain either a small or large reward. D1R Stimulation potentiated cue-driven action initiation, including fast impulsive actions on No-Go trials. By contrast, D1R blockade primarily disrupted the successful completion of Go trial sequences. Surprisingly, while after global D1R blockade this was characterized by a general retardation of reward-seeking actions, nucleus accumbens core (NAcC) D1R blockade had no effect on the speed of action initiation or impulsive actions. Instead, fine-grained analyses showed that this manipulation decreased the precision of animals’ goal-directed actions, even though they usually still followed the appropriate response sequence. Strikingly, such “unfocused” responding could also be observed off-drug, particularly when only a small reward was on offer. These findings suggest that the balance of activity at NAcC D1Rs plays a key role in enabling the rapid activation of a focused, reward-seeking state to enable animals to efficiently and accurately achieve their goal.